THE EFFECTIVENESS OF USING THE MATHEMATICS LEARNING COMPACT DISK RELATED TO SET MATERIAL ON THE LEARNING OUTCOMES IN MTs AL-FURQON SANDEN - Eko Budi Isnanto; Suparman Suparman (Universitas Ahmad Dahlan, 2017)
Learning mathematics is still dominated by the teachers and some students still assume that mathematics is a hard subject. The lack of variation in the implementation of learning mathematics can influence the results of students' mathematics learning. Fortunately, there is one way to improve the students learning outcomes which is by using Mathematics Learning CD (compact disk). The purpose of this study is to determine the learning outcomes between the students who use Mathematics learning CD with those who do not use CD. The study is done in MTs Al Furqon Sanden District Bantul. The population of this study was the seventh-grade students of MTs Al Furqon Sanden in School Year of 2015/2016, which comprises of 3 classes with a total of 64 students. The experiment class was VIIA and class VII Bas the control class that was selected by random sampling of classes. The methods of data collection using documentation and test. The research instrument is in the form of questions. The test instrument is used for validity, reliability and distinguishing features. Prerequisite test data analysis is used for Normality Test, Homogeneity Test, and Hypothesis Testing. Hypothesis test results with a significance level of 5% and 42 degrees of freedom showed that: (1) there are differences in learning outcomes of mathematics that using CD mathematics learning with the expository method. It can be seen in = 7.2809 and = 2,0183 so > and (2) Learning mathematics using CD is more effective than learning without using Mathematics CD. This is indicated by the = 7.1989 and = 7.2809, so > .